Absence of negative allelopathic effects of cylindrospermopsin and microcystin-LR on selected marine and freshwater phytoplankton species - Pinheiro, Carlos
Cyanobacterial toxins have been regarded by some researchers as allelopathic substances that could modulate the growth of competitors. Nevertheless, often the concentrations of toxins used are too high to be considered ecologically relevant. In this work we tested the hypothesis that microcystin-LR (MC-LR) and cylindrospermopsin (CYN) at ecologically relevant concentrations have no allelopathic effects on some species of phytoplankton. Extracts containing the toxins as well as pure MC-LR and CYN toxins were used to assess their effects on the growth rates of Nannochloropsis sp., Chlamydomonas reinhardtii, and Chlorella vulgaris. Cyanobacterial crude extracts induced more pronounced effects on growth rates than pure toxins. Microcystis aeruginosa and Aphanizomenon ovalisporum crude extracts containing MC-LR and CYN at 0.025-2.5 mg l(-1) stimulated growth rates of microalgae, whereas A. ovalisporum crude extracts containing 2.5 mg l(-1) of CYN strongly inhibited growth rates of microalgae after 4 and 7 days of exposure. MC-LR and CYN at environmentally occurring concentrations were unable to affect negatively the growth of microalgae, and therefore these molecules may play roles other than allelopathy in natural ecosystems.